Public confidence in the New South Wales criminal justice system: 2012 update - Craig Jones
This report assesses whether confidence in the New South Wales criminal justice system  has changed since 2007, whether changes in knowledge and/or punitiveness underpin any changes in confidence, and  whether confidence in police differs from confidence in the courts. Method: Repeat cross-sectional survey of the NSW public (n=2,002 in 2007; n=2,001 in 2012). The survey measured confidence, levels of knowledge and public demand for harsher sentencing in both years. Logistic regression models estimated changes in confidence after accounting for changes in sample composition. In 2012, participants were also asked about confidence in the police and courts separately. Results: Participants had high levels of confidence that the CJS respects the rights of the accused and treats them fairly but lower levels of confidence that the CJS brings people to justice, deals with cases promptly or meets the needs of victims. With the exception of confidence in respecting the rights of the accused, confidence was significantly higher in 2012 than in 2007. The 2012 respondents were also more knowledgeable about crime and justice and less punitive than the 2007 respondents. Respondents tended to have higher levels of confidence in the police than the courts. Conclusion: Levels of confidence in the CJS have improved since 2007. Factors such as increased knowledge and decreases in punitiveness may have contributed to these increases. However the changes in all three measures could reflect other factors such as the effect of the media and public policy. While confidence in police is generally high, the public lack confidence in the expediency of the courts and in outcomes for victims